PERTUNJUKAN KABARET OYOT GODHONG DI MIROTA BATIK YOGYAKARTA - Ni Luh Made Kartika Ratna Dewi (Greget, 2015)
The research entitled â€œThe Performance ofOyot GodhongCabaret in Mirota BatikYogyakartaâ€ is in the form of a qualitative descriptive analysis which uses a creative approach.The goal of the research is to describe analytically the form of the performance and the creativework of all those who support the Oyot Godhong Cabaret in Miroto Batik Yogyakarta. By applying a qualitative method with an analytical descriptive approach, the research findings show thatthe performance of the Oyot Godhong Cabaret is in the form of a dance and musical performancewhich is performed mainly by transgender artists with a group of backing dancers who present agroup composition with many variations. The structure of the performance consists of anopening(traditional Javanese) dance, which is separate from the main part of the performance.This is followed by the opening section of the Cabaret and the main performance, which is mainlyperformed using lip-synch, and the final section. The mood of the performance is lively, joyful,and interspersed with laughter. Based on the characteristics and entertaining nature of the performance, Oyot Godhong Cabaretmay be described as a form of Kitsch performance.Keywords: Cabaret, Transgender, and Creativity.